2020
DOI: 10.1021/acsami.0c00596
|View full text |Cite
|
Sign up to set email alerts
|

Design of Dendritic Large-Pore Mesoporous Silica Nanoparticles with Controlled Structure and Formation Mechanism in Dual-Templating Strategy

Abstract: Dendritic large-pore mesoporous silica nanoparticles (DLMSN) is an important biodegradable drug carrier due to its high porosity, which can be prepared by coassembly of a major template and an auxiliary template in aqueous solution, followed by hydrolysis of tetraethyl orthosilicate (TEOS). The auxiliary template is key to obtaining dendritic large-pore structures; however, how to choose the auxiliary template to obtain the desired pore structure is largely unknown. This is because the formation mechanism of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…DLMSNs were first prepared by a double template method that we previously reported. 20 304 mg of CTAB was added into 20 mL of double distilled water (DDW) containing 400 mg of TEA, and the mixture was stirred in an oil bath by a thermostat at 80 °C for 1 h. A total of 91.2 mg of DFX was then added, and the solution was stirred for 3 h. After that, 3.2 mL of TEOS was added to the above solution and further stirred for 20 min. The resulting solution was centrifuged at 15,000 rpm for 20 min, and the precipitate was washed several times with ethanol to obtain DLMSNs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DLMSNs were first prepared by a double template method that we previously reported. 20 304 mg of CTAB was added into 20 mL of double distilled water (DDW) containing 400 mg of TEA, and the mixture was stirred in an oil bath by a thermostat at 80 °C for 1 h. A total of 91.2 mg of DFX was then added, and the solution was stirred for 3 h. After that, 3.2 mL of TEOS was added to the above solution and further stirred for 20 min. The resulting solution was centrifuged at 15,000 rpm for 20 min, and the precipitate was washed several times with ethanol to obtain DLMSNs.…”
Section: Methodsmentioning
confidence: 99%
“…Dendritic large-pore mesoporous silica nanoparticles (DLMSNs) have attracted extensive attention and interest due to their faster degradation rate in vivo and larger-sized pores than mesoporous silica nanoparticles (MSNs). In our recent study, we reported a design strategy to prepare DLMSNs with the desired pore structure (size and shape) by using suitable auxiliary templates. A tunable pore structure with improved accessibility to the internal surface and easy chemical modification resulting from the presence of large amounts of active hydroxyl groups makes DLMSNs an ideal carrier material for selective loading or efficient co-loading of small molecules, biomacromolecules, and even NPs. , Hence, we intend to develop a multifunctionalized nanoplatform based on DLMSNs for combining the above-mentioned therapies against metastatic TNBC.…”
mentioning
confidence: 99%
“… 50 The DMSNs-NH 2 has a large pore size of 8.1 nm, a surface area of 449.1 m 2 g −1 , and a pore volume of 0.8 cm 3 g −1 , which are beneficial for loading and protecting plasmid DNA and increasing the delivery efficiency. 38 , 54 , 64 It is worth mentioning that according to literature, mesoporous silica nanoparticles with a hollow architecture showed higher loading efficiency than those with the same mesoporous morphology but no hollow architecture. 44 , 65 This reminds us that we can add the hollow architecture based on DMSNs-NH 2 in future research, which might be more helpful in improving the efficiency of loading and transferring the plasmid.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, we investigated the possibility of using dendritic mesoporous silica nanospheres (DMSNs), which possess a highly favorable structure and unprecedented smallest particle size in liquid chromatography, as an appealing packing material for nanopacking-driven ultra-high-efficiency separation. DMSNs is a newly emerging advanced material, showing unique structural features that allow it as an ideal nanopacking for HPLC, including monodispersed nanoscale particle size and center-radial centrosymmetric mesopore channels. These features will contribute to not only enhanced permeability of resulting packed columns but also reduced eddy diffusion (due to extreme uniformity in packing and diffusion paths).…”
Section: Introductionmentioning
confidence: 99%